A capitals framework for rural areas: 'Place-planning' the global countryside. (September 2022) - Gkartzios, Menelaos; Gallent, Nick; Scott, Mark
Abstract: Set in the context of debates over the future of rural areas, and the role of planning in co-delivering a sustainable, inclusive and resilient countryside, this article considers the value of a place capitals perspective for unpacking, firstly, 'what makes' rural places and, secondly, the ways that planning can ensure the protection, enhancement and sensitive use of those capitals. Rural places are presented as composites of built, economic, land-based and socio-cultural capitals and as possessing a 'spatial energy' that inheres in the linkages between capitals. Harnessing that 'spatial energy' is critical to co-producing better rural places. The paper aims towards a theorisation of rural places and planning that transcends jurisdictional boundaries and the peculiarities of planning systems. Building on existing scholarship, a 'capitals framework' is developed that has general applicability: it can be deployed flexibly as a means of understanding the 'inner workings' of rural place and as a guide for planning intervention. Highlights: We propose a capitals framework to theorise the relationship between planning and rural places. We discuss different forms of planning interacting with different forms of capital in rural areas. We visualize the relationship between rural places and planning through a 'Wheel of Place'. We examine 'place-planning' linkages in the global countryside irrespective of planning frameworks and rural definitions.